Analisis Laporan Keuangan dalam Mengevaluasi Kinerja Keuangan Antara Perusahaan pada Bank Pemerintah - Vletzia Thesman (Universitas 45 Surabaya, 2023)
This study aims to analyze financial statements in inter-company financial performance at state-owned banks. Financial performance is a critical factor for companies in the banking sector, especially state-owned banks that play a strategic role in supporting a country's economic stability. This study uses a quantitative approach by collecting financial data from several state-owned banks for the last five years. Traditional financial ratios such as profitability, liquidity, solvency and efficiency, as well as specific financial ratios for banking, such as the CAMELS ratio, were used for analysis. The results showed that there were significant differences in financial performance among the state-owned banks studied. Profitability and liquidity ratios are proven to be key factors in assessing the financial performance of state-owned banks. In addition, risk management and operational efficiency also contributed to the differences in performance among these banks.